2014
DOI: 10.1002/elps.201400049
|View full text |Cite
|
Sign up to set email alerts
|

Trends in proteomic analysis of human vitreous humor samples

Abstract: Proteomic analysis of human vitreous humor (VH) may elucidate the pathogenesis of retinal ocular diseases and may provide information for the development of potential therapeutic targets due to its pivotal location near lens and retina. The discovery of whole VH proteome involves a complex analysis of thousands of proteins simultaneously. Therefore, in proteomic studies the protein fractionation is important for reducing sample complexity, facilitating the access to the low-abundant proteins, and recognizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 117 publications
(554 reference statements)
0
21
0
Order By: Relevance
“…Thus, AH proteins that represent the pathophysiologic environment of the retina can also serve as biomarkers for disease conditions such as PDR and recognize them as biotargets for clinical research. 36 However, there are certain limitations associated with this study. The observation of less number of proteins in this study compared with previous published literature may be due to the collection of a small volume of samples and the collection at different clinical stages of PDR.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, AH proteins that represent the pathophysiologic environment of the retina can also serve as biomarkers for disease conditions such as PDR and recognize them as biotargets for clinical research. 36 However, there are certain limitations associated with this study. The observation of less number of proteins in this study compared with previous published literature may be due to the collection of a small volume of samples and the collection at different clinical stages of PDR.…”
Section: Discussionmentioning
confidence: 93%
“…Most recently, Skeie et al 11 identified over 2000 proteins in each of four anatomic vitreous compartments in postmortem human vitreous from nondiseased eyes using high-performance liquid chromatography (HPLC) coupled with electrospray ionization (ESI)-MS/MS. 1 These studies are more fully reviewed by Rocha et al 12 While these techniques yield a much larger number of proteins identified in vitreous, the prefractionation methods remain complex and the required sample volumes are excessive, making proteomic analysis of individual samples challenging. Further, despite the breadth of data generated by these investigations, a meaningful conceptual framework for understanding vitreous function has yet to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that these molecules have a relevant role in the reparative wound-healing process and retinal photoreceptor apoptosis in RRD, and consequently, may improve the post-surgical visual outcomes [ 12 ]. Also, the proteome and biochemical properties of vitreous are directly affected by physiological and pathological conditions of the retina [ 13 , 14 , 15 ]. So, vitreous is a suitable matrix for studying the pathophysiological mechanisms in the RRD.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative proteomics provides an additional approach to understand the global proteomic dynamics by identifying and comparing quantitatively several proteins in ocular fluids [ 16 , 17 ]. Although the application of proteomics technology in ophthalmic research is becoming increasingly common [ 15 , 18 , 19 ], the published information about vitreous proteome in RD is scarce. Indeed, the majority of these studies are focused on PVR [ 14 , 20 , 21 , 22 ] with the application of different proteomic techniques.…”
Section: Introductionmentioning
confidence: 99%